Knowledge Sources for Evidence-Based Practice in Rheumatology Nursing. (December 2015) - Neher, Margit; Ståhl, Christian; Ellström, Per-Erik; Nilsen, Per
As rheumatology nursing develops and extends, knowledge about current use of knowledge in rheumatology nursing practice may guide discussions about future knowledge needs. To explore what perceptions rheumatology nurses have about their knowledge sources and about what knowledge they use in their practice, 12 nurses working in specialist rheumatology were interviewed using a semi-structured interview guide. The data were analyzed using conventional qualitative content analysis. The analysis yielded four types of knowledge sources in clinical practice: interaction with others in the workplace, contacts outside the workplace, written materials, and previous knowledge and experience. Colleagues, and physicians in particular, were important for informal learning in daily rheumatology practice. Evidence from the medical arena was accessed through medical specialists, while nursing research was used less. Facilitating informal learning and continuing formal education is proposed as a way toward a more evidence-based practice in extended roles.